A Dakota Cultural Intervention's Influence on Native Students' Sense of Belonging: A CBPR Case Study - Heather J. Peters; Teresa R. Peterson; The Dakota Wicoḣaƞ Community (SAGE Publishing, 2024)
This community-based participatory research case study demonstrates how Dakota Wicoḣaƞ utilized Indigenous and feminist epistemologies to create, implement, and evaluate a cultural intervention, the Mni Sota Makoce: Dakota Homelands Curriculum, to increase Native 6th- and 10th-grade social studies students' peoplehood sense of belonging (Tachine et al., 2017). Findings demonstrate Native students liked the curriculum and reported an increase in support and a decrease in invalidation of their sense of belonging. While the curriculum provided a source of racial-ethnic socialization, some European American students criticized the curriculum, which likely negatively impacted 6th-grade students psychological sense of school membership (Goodenow, 1993). Results indicate Indigenous culture, epistemologies, and pedagogies should be infused throughout all curricula, teachers need to be prepared to effectively deal with racist and discriminatory behavior, and Indian education is important to Native students' belonging. Implications and recommendations for funders, schools, researchers, teacher education programs, and Native communities are discussed.